2002
DOI: 10.1088/0967-3334/23/4/309
|View full text |Cite
|
Sign up to set email alerts
|

Recording of ENGs from the nerves innervating the pancreas of a dog during the intravenous glucose tolerance test

Abstract: Electroneurograms (ENGs) from the vagus nerve (VN), the splanchnic nerve (SN) and the pancreatic nerve (PN) innervating the pancreas of a dog, were recorded with chronically implanted 33-electrode spiral cuffs (cuff) before and after the pancreas were stimulated with intravenously (i.v.) administered glucose. In the cuffs platinum electrodes were arranged in three parallel spiral groups containing 11 electrodes on the inner surface. The cuffs had an inner diameter of 2 mm and a length of 18 mm. In a two-year s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Pancreatic function and vascular tone are controlled by autonomic nervous system supply acting upon the asymmetric vascular supply of the right and left pancreatic lobes ( Cadet‐Leite 1973 , Neuhuber 1989 , Spaulding 1997 , Rozman et al . 2002 , de Lahunta & Glass 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic function and vascular tone are controlled by autonomic nervous system supply acting upon the asymmetric vascular supply of the right and left pancreatic lobes ( Cadet‐Leite 1973 , Neuhuber 1989 , Spaulding 1997 , Rozman et al . 2002 , de Lahunta & Glass 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic functions are controlled by the autonomic nervous system, directly and indirectly ( Holmgren & Olsson 2011 , Rozman et al . 2002 , Seoane‐Collazo et al . 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…J. (3) Carbon nanofibers allowed assessment of issues of being focal and minimally invasive, and having enough stiffness for insertion [36]; (4) Laser-cut metal tracks and contacts embedded in silicone rubber in the transverse and longitudinal section of the nerve in front of selected bundles of fibers is a good compromise between resolution and industrial manufacturing [37], pre-strained silicone sheets with multi-contact (up to 33) which reliability was assessed in dogs for six months [38]; (5) TEENI concept [39] is an alternative approach that tends to promote nerve reconstruction in a tube of biocompatible hydrogel along a network of longitudinal planar electrodes in the case of amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, cuff electrodes are made of two to three metal rings around the epineurium, and most of the further evolutions focused on improving either their selectivity or the signal-to-noise ratio. At least five alternatives have been proposed: (1) flat interface nerve electrodes (FINE) gave promising results, even for long-term recordings [32]; (2) thin-film longitudinal intrafascicular electrodes (tfLIFE), and transverse intrafascicular multichannel electrodes (TIME), whose potential for selective stimulation and recordings was investigated using thin-film polyimide substrates [33][34][35]; (3) carbon nanofibers allowed assessment of focal and minimally invasive issues, with enough stiffness for insertion [36]; (4) laser-cut metal tracks and contacts embedded in silicone rubber in the transverse and longitudinal section of the nerve in front of selected bundles of fibers is a good compromise between resolution and industrial manufacturing [37], and pre-strained silicone sheets with multicontact (up to 33), in which reliability was assessed in dogs for six months [38]; (5) the TEENI concept [39] is an alternative approach that tends to promote nerve reconstruction in a tube of biocompatible hydrogel along a network of longitudinal planar electrodes in the case of amputation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rozman et al [112] demonstrated neural recording from the nerves innervating the pancreas and proposed using such recordings to achieve closed-loop controlled secretion of pancreatic hormones. As discussed in the last section, there are no reported applications of neural recording ICs for any chronically implantable PNS neuroprosthesis.…”
Section: Applications Of Neural Amplifiersmentioning
confidence: 99%